Effect of the bone marrow mesenchymal stromal cells cytokine-producing activity on mobilization of hematopoietic stem cells - E. A. Poponina; A. O. Pestrikova; E. L. Nazarova; N. V. Isaeva; E. S. Fokina; A. I. Endakova; N. V. Minaeva (Медицинская иммунология, 2024)
Hematopoietic stem cell transplantation is used to treat hemoblastoses and some other diseases. Depending on the diagnosis, autologous cells of the patient or allogeneic cells obtained from a healthy related or unrelated donor are used. A sufficient count of harvested hematopoietic progenitor cells is necessary for successful transplantation. Currently, stimulation of their egress from the bone marrow into the peripheral blood by a granulocyte colony-stimulating factor, followed by collection by leukapheresis, is widely used for their preparation. Hematopoietic stem cells leave the bone marrow niche formed by the stromal microenvironment when their holding bonds are interrupted. Mesenchymal stromal cells regulate the release of hematopoietic precursors by producing various cytokines and other biologically active substances. Therefore, the study of the functional properties of bone marrow mesenchymal cells can help in solving the problem of “poor” mobilizations that occur in patients with multiple myeloma.The aim of the study was to estimate the effectiveness of mobilization of hematopoietic stem cells depending on the cytokine-producing ability of mesenchymal stromal cells in the bone marrow of donors and patients with multiple myeloma.The yields of hematopoietic progenitors were studied in 10 donors (median age 27 years) and 18 patients with multiple myeloma (median age 57 years). In donors, the release of hematopoietic stem cells into the peripheral blood was stimulated by subcutaneous administration of G-CSF at a dose of 10 μg/kg/day. Patients with multiple myeloma received vinorelbine at a dose of 35 mg/m2 of body surface, followed by administration of G-CSF (10 μg/kg/day subcutaneously). A culture of mesenchymal stromal cells was obtained from bone marrow taken prior to mobilization and the content of interleukins IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α and IFN-γ in supernatants was studied by enzyme-linked immunosorbent assay using kits of reagents produced by Vector-Best (Novosibirsk).Patients with multiple myeloma were characterized by high secretion of the pro-inflammatory cytokine IL-2 (4.70 pg/ml vs 3.55 pg/ml in healthy individuals, p=0.003) and low IFN-γ (0.41 pg/ml vs 2.14 pg/ml in healthy, p<0.001), but no relationship was found between these cytokines and the hematopoietic stem cells yield. The present study showed that in patients with ineffective harvesting of hematopoietic precursors, secretion of IL-8 by stromal cells was low (308.08 pg/ml vs 561.29 pg/ml in healthy individuals, p=0.04).The obtained results are consistent with the literature data on the important role of IL-8 in the mobilization of hematopoietic stem cells, which allows to consider IL-8 as an informative marker for predicting the insufficient yields of hematopoietic precursors.